The Instituto Indigenista Interamericano. Continuities and fractures of the Mexican indigenist politics: ’modernization’ of the indigenous - Castillo Ramírez, Guillermo (Revista de Antropología Social, 2021)
Within the framework of the indigenist policy of the Mexican government of Ávila Camacho, this work argues that the process of “modernization”, understood as an exogenous cultural change designed and carried out by the anthropology, was the axis of the work program of the Instituto Indigenista Interamericano (III) (1942-1948). The main goal of this institute was “modernization” as the main route to improve the living conditions of indigenous groups and “incorporate” them into national society. First, this work traces the roles of Departamento Autónomo de Asuntos Indígenas (DAAI) and Congreso Indigenista Interamericano (CII) (1940) as antecedents of the formation and work´s program of the III. Later, this work explores the function of the III in relation with the Mexican State. This work has two main contributions. (1) The political-historical analysis that some of the central conceptual and ideological elements of the III were the DAAI and CII. (2) The description of the modernization, understood as structural change in the material culture and Indian way of life, was one of the main axes from the work program of the III.